Pengaruh Brand Image dan Perceived Value Terhadap Keputusan Pembelian dalam Berlangganan Layanan Netflix - Rani Haryanti; Donant Alananto Iskandar (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The research aims to determine how much effect brand image and perceived value of purchase decision on subscribing Netflix service. The research is a quantitative and use SPSS ver. 13 program with a total sample is 101 respondents who are Students from Kalbis Institute. The rea\search is using probability sampling and purposive sampling technics. The results of this research is brand image and perceived value effected to purchase decision. The benefits from this research as input evaluation and consider to keep brand im age and perceived value of Netflix strategic to compete with other competitor’s.